2021
DOI: 10.21037/tcr-21-1802
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG3 promotes the progression of clear cell renal cell carcinoma via regulating BIRC5 expression

Abstract: Background: Research has shown that the progression of clear cell renal cell carcinoma (ccRCC) is modulated by long non-coding RNAs (lncRNAs). However, the roles of specific lncRNAs in the malignancy of ccRCC are still unknown.Methods: TCGA and GSE66272 datasets were used to predict differentially expressed genes (DEGs) in ccRCC. ENCORI database was employed to display BIRC5 miRNA network and potential lncRNA interactions for miRNAs. KM plotter and correlation analyses were performed to identify the overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…When highly expressed, BIRC5 allows cancer cells to resist apoptotic checkpoints and anticancer agents [ 18 ]. Xu et al also demonstrated BICR5 is related with the development of ccRCC, which is consistent with our results [ 19 ]. BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) has the ability to modulate the spindle assembly checkpoint (SAC) family [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…When highly expressed, BIRC5 allows cancer cells to resist apoptotic checkpoints and anticancer agents [ 18 ]. Xu et al also demonstrated BICR5 is related with the development of ccRCC, which is consistent with our results [ 19 ]. BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) has the ability to modulate the spindle assembly checkpoint (SAC) family [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although most results correspond with other works, there were some discrepancies in the direction of change in expression, namely in SNHG3 and LINC00887. While SNHG3, an autophagy-related lncRNA (Xuan et al 2021), was downregulated in our study, other works show its upregulation in RCC (Zhang et al 2019;Yang et al 2020;Xu et al 2021). Similarly, LINC00887 was downregulated in our study and up-regulated in study of Wu et al (Wu et al 2022a).…”
Section: Discussionsupporting
confidence: 51%
“…SNHG3 promotes ccRCC cell proliferation through a TOP2A-dependent pathway ( Zhang et al, 2019 ). Baculoviral inhibitor of apoptosis repeat-containing 5 (BIRC5) is another regulatory target of lncRNA SNHG3 in ccRCC ( Xu et al, 2021c ). Cuproptosis-related lncRNAs can participate in the regulation of tumorigenesis and progression by binding to DNA, miRNA, and proteins, thereby affecting tumor progression, patient prognosis, and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%